OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY TO DETECT AND MONITOR NONEXUDATIVE NEOVASCULARIZATION IN AGE-RELATED MACULAR DEGENERATION - Manuel A P Vilela (Indonesian Vitreoretinal Society, 2021)
OCT angiography has improved the ability to identify silent or nonexudative neovessels in age-related macular degeneration. This promotes a rapid advancement in the diagnosis and in the necessity to expand our management decisions. This context is presented and the biomarkers are discussed.